# Negation implies Negation of Conjunction/Case 1

Jump to navigation
Jump to search

## Theorem

- $\neg p \implies \neg \left({p \land q}\right)$

## Proof

By the tableau method of natural deduction:

Line | Pool | Formula | Rule | Depends upon | Notes | |
---|---|---|---|---|---|---|

1 | 1 | $\neg p$ | Assumption | (None) | ||

2 | 2 | $p \land q$ | Assumption | (None) | ||

3 | 2 | $p$ | Rule of Simplification: $\land \mathcal E_1$ | 2 | ||

4 | 1, 2 | $\bot$ | Principle of Non-Contradiction: $\neg \mathcal E$ | 3, 1 | ||

5 | 1 | $\neg \left({p \land q}\right)$ | Proof by Contradiction: $\neg \mathcal I$ | 2 – 4 | Assumption 2 has been discharged | |

6 | $\neg p \implies \neg \left({p \land q}\right)$ | Rule of Implication: $\implies \mathcal I$ | 1 – 5 | Assumption 1 has been discharged |

$\blacksquare$

## Sources

- 1964: Donald Kalish and Richard Montague:
*Logic: Techniques of Formal Reasoning*... (previous) ... (next): $\text{II}$: 'AND', 'OR', 'IF AND ONLY IF': $\S 3$: Theorem $\text{T43}$